Corporate Liability and Human Rights Protection in ASEAN Anti-Corruption Law - Emiliya Febriyani; Salwa Zolkaflil; Antony Antony; Tantimin Tantimin; Rufinus Hotmolana Hutauruk (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
Corruption involving collusion between public officials and corporate actors raises a legal problem because it not only causes state financial losses but also harms public interests and may violate human rights. Anti-corruption laws that focus excessively on state financial loss may overlook the broader impact of corruption on public welfare, public safety, environmental protection, and fairness in public procurement. This research aims to analyze corporate liability in public-sector corruption and compare the legal frameworks of Indonesia, Malaysia, and Vietnam. This study applies normative legal research using statutory and comparative approaches. The data are analyzed descriptively and analytically through primary legal materials from each jurisdiction. The findings show that Indonesia has the most significant normative gaps due to lenient corporate sanctions and the dominance of the state financial loss doctrine. Malaysia provides a stronger framework for corporate liability but remains largely oriented toward financial recovery. Vietnam offers the most comprehensive framework because it covers non-state actors and recognizes compensation for damages caused by corruption, although further substantive mechanisms are still needed. This research recommends strengthening anti-corruption norms by prioritizing public interests and integrating human rights considerations into corporate liability.